2006
DOI: 10.1111/j.1540-8167.2006.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Improves Abnormal Repolarization and Contraction in Left Ventricular Myocytes of Dogs with Heart Failure by Inhibiting Late Sodium Current

Abstract: Ranolazine significantly (P<0.05) and reversibly shortened the APD of myocytes stimulated at either 0.5 or 0.25 Hz in a concentration-dependent manner. At a stimulation frequency of 0.5 Hz, 5, 10, and 20 microM ranolazine shortened the APD(90) (APD measured at 90% repolarization) from 516+/-51 to 304+/-22, 212+/-34 and 160+/-11 ms, respectively, and markedly decreased beat-to-beat variability of APD(90), EADs, and dispersion of APDs. Ranolazine preferentially blocked I(NaL) relative to I(NaT) in a state-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
241
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(271 citation statements)
references
References 31 publications
25
241
2
3
Order By: Relevance
“…Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202]. In conditions of cardiac ischemia/reperfusion, inhibition of I NHE preserved mitochondrial energetics (i.e., ATP and PCr content) [111,162].…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202]. In conditions of cardiac ischemia/reperfusion, inhibition of I NHE preserved mitochondrial energetics (i.e., ATP and PCr content) [111,162].…”
Section: Discussionmentioning
confidence: 99%
“…The high probability of formation of EAD, leading to TdP, during HF has been experimentally demonstrated [7] but few studies have addressed the role of I NaL in such situations [18,26,61]. Our results are in keeping with experimental findings, in which the I NaL blocker ranolazine, effectively suppresses EADs from ventricular myocytes from failing hearts [18,23]. Furthermore, during conditions of reduced repolarization reserve, in which outward K + currents are inhibited by drugs or by diseases, results of experimental studies [21][22][23]62] have unmasked the role of endogenous or enhanced I NaL in exerting proarrhythmic effects.…”
Section: Important Role Of I Nal During Heart Failure and Clinical Immentioning
confidence: 99%
“…Major changes in intracellular and sarcoplasmic reticulum (SR) Ca 2+ homeostasis are also associated with HF in several animal species, included human [9,[11][12][13]. In myocytes from failing hearts [Na + ] i concentration and Ca 2+ handling are closely linked; [Na + ] i is increased in failing ventricular myocytes from human and other animal species [3,4,9,14] and a prominent increase of the human late Na + current (I NaL ) has also been documented [15,16], and has been proposed as a therapeutic target [17][18][19]. Experimental studies have shown that the I NaL is involved in the generation of EADs in myocytes [17,18] and life-threatening arrhythmias, such as torsade de pointes (TdP) [20], especially under conditions of reduced repolarization reserve in several animal species [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] By this inhibition, it affects intracellular calcium handling, producing an energy sparing effect. 24 Ranolazine induces post repolarization refractoriness in atrial tissue and is a potent inhibitor of after depolarizations produced by a number of mechanisms, [25][26][27][28] an effect that could reduce pulmonary vein firing. As such, ranolazine should prove to be particularly useful in the treatment of AF.…”
Section: 2mentioning
confidence: 99%